Perbandingan Kelengkapan Resep Secara Administratif pada Resep Elektronik dan Resep Manual di Poli Anak Eksekutif Rumah Sakit X Kemayoran Periode Oktober – Desember 2023 - Salwa Aulia Afifah; Anna Uswatun Hasanah Rochjana; Sylvi Adiana (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Prescription review is an important first step before the distribution process is carried out, where the aim of checking the prescription is to ensure that all aspects, both administrative and pharmaceutical, are appropriate. This research aims to determine the percentage of administrative completeness for electronic prescriptions and manual prescriptions, and to compare the completeness between the two for the period October to December 2023. The method used in this research is quantitative descriptive. The research results showed that the completeness of electronic prescription administration included the inclusion of the patient's name, patient's age, doctor's name, doctor's practice address, prescription date, and the room where the prescription came from for a total of 389 prescription sheets (100%). Meanwhile, the completeness of manual prescription administration includes the patient's name, doctor's name, doctor's SIP, doctor's practice address, and prescription date for a total of 337 prescription sheets (100%). Based on a comparison of the percentage of administrative completeness between electronic prescriptions and manual prescriptions in the period October – December 2023, electronic prescriptions show better completeness in terms of patient name, patient age, doctor's name, doctor's practice address, date of prescription, and room where the prescription came from (100% ), patient weight (55.78%), and doctor's SIP (87.92%). On the other hand, manual prescriptions show better completeness in terms of patient name, doctor's name, doctor's SIP, doctor's practice address, and prescription date (100%), patient's age (40.36%), patient's weight (86.35%). %), and doctor's initials (27.89%).